2008
DOI: 10.5194/angeo-26-941-2008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chaotic aspects of magnetosphere under various physical conditions using AE index time series

Abstract: Abstract. The deterministic chaotic behaviour of magnetosphere was analyzed, using AE index time series. The significant chaotic quantifiers like, Lyapunov exponent, spatiotemporal entropy and nonlinear prediction error for AE index time series under various physical conditions were estimated and compared. During high solar activity (1991), the values of Lyapunov exponent for AE index time series representing quiet conditions (yearly mean = 0.5±0.1 min −1 ) have no significant difference from those values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…The ionosphere is a system that can also be described by similar dynamical processes as the magnetosphere, as both systems are also coupled (Unnikrishnan, 2010). Some of the investigations carried out on the chaoticity of both the ionosphere and the magnetosphere have yielded similar results for storm and quiet periods (Unnikrishnan, 2008(Unnikrishnan, , 2010. It implies that one can use similar methods to study the ionosphere and magnetosphere, and this informs the use of Tsallis entropy to study the ionosphere in this work, since it has been used to describe the magnetosphere.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The ionosphere is a system that can also be described by similar dynamical processes as the magnetosphere, as both systems are also coupled (Unnikrishnan, 2010). Some of the investigations carried out on the chaoticity of both the ionosphere and the magnetosphere have yielded similar results for storm and quiet periods (Unnikrishnan, 2008(Unnikrishnan, , 2010. It implies that one can use similar methods to study the ionosphere and magnetosphere, and this informs the use of Tsallis entropy to study the ionosphere in this work, since it has been used to describe the magnetosphere.…”
Section: Discussionsupporting
confidence: 53%
“…This is also evident in the study on magnetospheric dynamics and the ionosphere in the past decade. The study of chaos in magnetospheric index time series such as the AE index and the AL index was initially conducted by Vassiliadis et al (1990), Shan et al (1991), Pavlos et al (1992) and Unnikrishnan (2008). These efforts have led to further advances in the study of chaos in the upper atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…time delayed mutual information and the false nearest neighbour method), it is observed that any delay tZ25 and any dimension mZ3 are the suitable choices for t and m, respectively, for both IMF 9B9 and B z time series. By repeating the similar analysis for all the time series considered in the present study, these choices for t and m are found to be true (Unnikrishnan et al, 2006a(Unnikrishnan et al, , 2006bUnnikrishnan, 2008). Hence, the choice of t as 40 and m as 4 for further analysis of this study are reasonable.…”
Section: Resultsmentioning
confidence: 85%
“…Unnikrishnan (2008) observed that during high solar activity (1991), the values of Lyapunov exponent for AE index time series, representing the magnetopseric dynamics for quiet conditions have no significant difference from the corresponding storm conditions. This implies that geomagnetic storms may not be an additional source to increase or decrease the deterministic chaotic aspects of magnetosphere during high solar activity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation